AKTIVITAS PEMANASAN DAN PENDINGINAN PADA SISWA EKSTRAKURIKULER OLAHRAGA DI SMP NEGERI SE- KECAMATAN SEMARANG TIMUR KOTA SEMARANG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
Purpose of this study was to maximize performance and minimize the risk of injury . This research is a qualitative descriptive analysis of the percentage approach , while the data collection methods used by the researchers are observation, questionnaire, interviews, and documentation. The results of the calculation of the questionnaire showed a general warming up and stretching activities in both categories at all ( 59.71 % ), whereas the activity of specific warming up in enough categories ( 50.36 % ), and activity sufficient warming down in the category ( 48.92 % ). It can be concluded that, activity warming up and warming down in extracurricular sports students in Junior High School as the Kecamatan Semarang Timur is good enough. It's just a lot of factors that make the implementation was not optimal, such as a lack of supervision of the coach when the students warmed up, the lack of knowledge of students about the functions and benefits of warming and cooling, the duration of the activity and the lack of heating and cooling is done.